2004
DOI: 10.1016/j.virol.2003.09.014
|View full text |Cite
|
Sign up to set email alerts
|

In vivo neutralization of hepatitis B virus infection by an anti-preS1 humanized antibody in chimpanzees

Abstract: Previously, we generated a murine monoclonal antibody (mAb), KR127, that recognizes amino acids (aa) 37-45 of the preS1 of hepatitis B virus (HBV). In this study, we have constructed a humanized version of KR127 and evaluated its HBV-neutralizing activity in chimpanzees. A study chimpanzee was given a single intravenous dose of the humanized antibody, followed by intravenous challenge with adr subtype of wild type HBV, while a control chimpanzee was only challenged with the virus. The result showed that the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 36 publications
0
56
0
Order By: Relevance
“…Alanine-scanning mutagenesis of residues 2P-10P of the preS1 epitope showed that mutations in residues 2P and 5P-10P caused a significant decrease in antibody binding, whereas mutations in Ser3P and Asp4P did not have any effect (16). In particular, mutations at Asp7P and Trp8P completely impaired the antibody binding (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alanine-scanning mutagenesis of residues 2P-10P of the preS1 epitope showed that mutations in residues 2P and 5P-10P caused a significant decrease in antibody binding, whereas mutations in Ser3P and Asp4P did not have any effect (16). In particular, mutations at Asp7P and Trp8P completely impaired the antibody binding (16).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we generated an anti-preS1 murine antibody KR127 that recognizes adr subtype preS1 (residues 37-45) (15). KR127 and the humanized version of KR127 antibody (HzKR127) bind to the preS1 domain of various clinical HBV isolates, including both adr and ayw subtypes, suggesting their broad neutralizing activity (15,16). HzKR127 also has been shown to exhibit in vivo neutralizing activity in chimpanzee and to protect the chimpanzee from HBV infection (16), indicating the high potential of the antibody for the immunoprophylaxis of HBV infection and therapy of hepatitis.…”
mentioning
confidence: 99%
“…Chimpanzee is the only natural host that allows active replication of HBV. [5][6][7] Although this animal is a valuable model for the study of hepatitis viruses, 8 the practical use of chimpanzees is severely limited both ethically and economically.Several small animal models of HBV infection have been reported. The HBV transgenic mouse is a very useful model for the study of virology and evaluation of antiviral drugs.…”
mentioning
confidence: 99%
“…Previously, we generated HzKR127, a humanized version of anti-preS1 murine monoclonal antibody KR127 that binds adr subtype preS1 (residues 37-45) [10]. The antibody exhibits broadly neutralizing activity against various HBV isolates, including adr and ayw subtypes, and protected the chimpanzee from HBV infection [10].…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling of the binding site through large conformational changes can significantly expand the structural diversity of the primary repertoire beyond a certain limit that calculated from sequence diversity alone, making it possible to bind an unlimited number of antigens in primary response. Although HzKR127 was originated from murine KR127 generated after multiple immunizations [10], the CDRs of HzKR127 still retain high sequence similarity with those of germline antibody for murine KR127. Furthermore, the HzKR127 Fab also shows very high sequence homology with other murine germline antibodies 48G7, 28B4, and 7G12.…”
Section: Introductionmentioning
confidence: 99%